Pengembangan Instrumen Tes PLSV Berdasarkan Indikator Berpikir Kritis dan Pemecahan Masalah - Nur Agustiani; Ana Setiani; Hamidah Suryani Lukman (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
This study aims to develop a test instrument of linear equation in one variable based on critical thinking and problem-solving indicators, which validate by experts. The type of this research is R D research with the ADDIE model. This study is limited only to Analysis (Analysis), Design (Design), and Development (Development). The instrument used in this study was an expert validation sheet. This study involved five mathematics lecturers as validators. The expert validation data were analyzed using V'Aiken. The results of the study indicate that the average value of the V'Aiken index for the feasibility of the content aspect is 0.92, with very high criteria. The feasibility of the linguistic aspect is 0.92 with very high criteria; conformity with the critical thinking indicator is very high with a value of 0.90 for questions number 1, 2, and 4, and for item number 3 is 0.91. The suitability of the solution indicator is very high, with a value of 0.89 for questions number 1, 2, and 4, and for item number 3, it is 0.90. Overall, the test instrument developed is very feasible to use.